MAKANAN TABU DI JENEPONTO SULAWESI SELATAN - Dadang Sukandar (Food and Nutrition Society of Indonesia, 2007)
Food taboo is one of nutrition problem in Indonesia. Solution to overcome this problem is therefore needed. Objectives of this study are to identify taboo foods and to reduce community food taboo beleive through conducting training on basic nutrition knowledge. Study was conducted in Jeneponto South Sulawesi from December 1995 to November 2006. A sample of size 45 households was drawn randomly from household population of size 226. The households population is household farmer who are beneficiary of Special Program for Food Secutity, Food and Acgriculture Organization. Data were analyzed quantitatively and qualitatively and presented in one way table. Results show that groups which had a large number of food taboo were pregnant women group. There are 20 taboo foods for pregnant women and 7 taboo food for lactating mother. Some taboo foods for pregnant women are squid, pari fish, toka-toka fish, papaya, pineapple, etc. Some taboo foods for lactating mother are chicken, chili, shrimp, pari fish, etc. After attending trainning, the knowledge on basic nutrition knowledge of the farmers increase significantly, therefore it is hoped that their knowledge can reduce their belive of the food taboo.